Core Tax Administration System and Transformation of Risk-Based Taxpayer Compliance Supervision in Indonesia - Rahmat Burhamzah; Deddy Ibrahim Rauf; Muhammad Rijal Alim Rahmat (Economics and Business Journal (ECBIS), 2026)
Digital transformation is an important agenda in tax administration reform in Indonesia. One of the strategic steps taken by the Directorate General of Taxes (DGT) is the implementation of the Core Tax Administration System (CTAS) as a core system that integrates all tax administration processes. This study aims to examine the role of CTAS in strengthening taxpayer compliance supervision in Indonesia. The research uses a qualitative descriptive approach by utilizing secondary data in the form of DGT performance reports, official publications, and literature related to tax modernization. The analysis was carried out by examining changes in administrative processes, data management, and supervision patterns after the implementation of CTAS. The results of the study show that CTAS plays a role in improving the quality and integration of tax data, strengthening risk-based supervision, and supporting more systematic compliance monitoring. However, the effectiveness of the implementation of CTAS still faces challenges, especially related to the readiness of human resources and the equitable distribution of technological infrastructure.